Creating Innovative Banking Products Through Digitalization of Banking Services - Rakhimdjanovna, Yunusova Shakhlo (Research Parks Publishers, 2023)
The article covers issues of digitization of banking services and their possibilities as a result of modern banking technologies, relations of foreign and local economists about innovative products, analysis of retail banking practices in Uzbekistan and opportunities of important financial technologies in the world. In addition, the author's conclusions and suggestions on creating innovative banking products and improving them through the digitization of banking services have been developed.